Application of the Kahoot game-based problem-based learning model to increase motivation and learning achievement in the calculus - Muhassanah, Nur'aini; Kartika, Dwiani Listiya (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study is to raise student achievement and learning motivation by implementing problem-based learning based on the Kahoot game. This research was carried out from February to April 2023. This type of research is classroom action research, which consists of 2 cycles, each with four stages: planning, implementing, observing, and reflecting. This research was conducted on 12 students of the mathematics study program, even in the semester 2022/2023, who took the Calculus 2 course. Data collection techniques were tests and observations. The results of this research are as follows: 1) There was an increase in learning achievement after implementing the Kahoot game-based problem-based learning model seen from the class average before learning. 57.87 and after cycles I and II, with a class average of 71.5 and 80.25. 2) increase student learning motivation. This is indicated by the results of the learning motivation data before the research, which met the good enough criteria; as many as seven students (58.33%) and five students (41.67%) met the good criteria. After taking action, eight students (66.67%) fell into the good criteria, and four (33.33%) fell into the very good criteria.